Marxist philosophy and its influence on today's world - Kien, Pham Thi (Kalágatos, 2025)
In the context of the world facing a series of solid problems such as economic inequality, labor exploitation, environmental crisis, as well as the concentration of wealth and power, Karl Marx's thought is once again recognized as an important tool to solve any problem and propose solutions for transformation. The content of Marxism lies in the historical materialist perspective, the economic foundation determines the process of forming political, cultural and ideological institutions, and emphasizes the role of conflict in the content level and consistency in the main meaning for the history of the process. Through the historical materialist methodology and demonstrative analysis, this study focuses on evaluating the arguments put forward by Marx in his critique of capitalism and considering their appropriateness when applied to the current socio-economic context. The results show that the core principles of Marxism still hold value as a compass, helping to identify any work in society and orienting practice activities towards justice and equality.